RONC-08. HIGHER PSEUDOPROGRESSION RATES AFTER PROTON VERSUS PHOTON RADIOTHERAPY IN PEDIATRIC PATIENTS WITH LOW-GRADE GLIOMA. Issue 2 (22nd June 2018) - Ludmir, Ethan; Mahajan, Anita; Paulino, Arnold; Jones, Jeremy; Ketonen, Leena; Ater, Joann; Su, Jack; Grosshans, David; Adesina, Adekunle; Dauser, Robert; Weinberg, Jeffrey; Chintagumpala, Murali
Abstract: Pseudoprogression (PsP), a recognized post-radiotherapy (RT) phenomenon for high-grade glioma, is poorly characterized for low-grade glioma (LGG). Serial MRI scans of 83 pediatric LGG patients managed at two institutions between 1998 and 2017 were evaluated for PsP. 32 patients (39%) were treated with photon-based intensity-modulated RT (IMRT), and 51 (61%) were treated with proton beam therapy (PBT). The median age at time of RT was 10.0 years (range 1.0 - 17.2). The most common diagnoses were pilocytic astrocytoma (50/83, 60%) and grade 2 astrocytoma (22/83, 27%). No differences in age at RT, RT dose, treatment volume, or histology were identified between the IMRT and PBT groups. Post-RT radiographic tumor enlargement consistent with PsP was identified in 31/83 patients (37%), including 8/32 IMRT patients (25%) and 23/51 PBT patients (45%); PBT patients were more likely to have post-RT enlargement (HR 2.10, p=0.048). The enlargement peaked at a median of 4 months after RT (range 1-8 months), with a median increase of 22% (range 5-259%). Median time to stabilization was 12 months, with a median of 15 and 9.5 months for the IMRT and PBT cohorts, respectively (p=0.001). Confirmed local progression occurred in 10 patients: 7/32 IMRT patients (22%) and 3/51 PBT patients (6%). These data highlight substantial rates of PsP among patients treated with PBT, and further follow-up may elucidate whether these higher rates of PsP are associated with improved local disease control. PsP should be considered when assessing response to RT in LGG, particularly within the first year after RT.